2019
DOI: 10.3389/fendo.2019.00177
|View full text |Cite
|
Sign up to set email alerts
|

Overt and Subclinical Hypothyroidism in the Elderly: When to Treat?

Abstract: Hypothyroidism is characterized by increased thyrotropin (TSH) levels and reduced free thyroid hormone fractions while, subclinical hypothyroidism (sHT) by elevated serum TSH in the face of normal thyroid hormones. The high frequency of hypothyroidism among the general population in Western Countries made levothyroxine (LT4) one of the 10 most prescribed drugs. However, circulating TSH has been demonstrated to increase with aging, regardless the existence of an actual thyroid disease. Thus, when confronting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 76 publications
0
47
0
Order By: Relevance
“…There is a plausible explanation that hypothyroidism reduces dopaminergic activity in central nervous system, which in turn increases norepinephrine leading to hypertension. Several statistical analyses were undertaken based on this theory, but we found no significant association between hypothyroidism and hypertension (Table-3 As regards to age, it has been observed that TSH increased with age [5,26] though with much genetic variation. We found that age had no significant correlations with TSH and FT4 (Table-5, Figure 1).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There is a plausible explanation that hypothyroidism reduces dopaminergic activity in central nervous system, which in turn increases norepinephrine leading to hypertension. Several statistical analyses were undertaken based on this theory, but we found no significant association between hypothyroidism and hypertension (Table-3 As regards to age, it has been observed that TSH increased with age [5,26] though with much genetic variation. We found that age had no significant correlations with TSH and FT4 (Table-5, Figure 1).…”
Section: Discussionmentioning
confidence: 95%
“…Hypothyroidism is a common endocrine problem that is encountered everywhere in the world, be it in developed or developing countries [1][2][3]. This endocrine disorder affects health from utero to childhood and even extends to adulthood [4,5]. Hypothyroidism in pregnancy may lead to premature delivery or even its loss [6].…”
Section: Introductionmentioning
confidence: 99%
“…According to Calsolaro V, et al 'The high frequency of hypothyroidism among the general population in Western Countries made levothyroxine (LT4) one of the 10 most prescribed drugs.' (3) Individuals from all age groups and both sexes, irrespective of young or old can be affected, especially in elderly individuals the clinical features may be atypical, and the diagnosis easily missed (4) and studies have shown that as much as 4.8% of elderly can have thyroid disorders. (5) Yet this disease has not been fully understood i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This is higher than the upper limit of the diagnostic reference range defining the disease, which for most assays is approximately 4 mIU/L 7. This elevated decision point setting appears to stem from a desire to minimise the application of therapy in patients who may not require it 7,67,68. Accordingly, as for indicating treatment of hypothyroidism, clinicians are left with a paradox that establishing a diagnosis of subclinical hypothyroidism no longer implies that the disease may warrant treatment.…”
Section: Laboratory-based Definition Of Hypothyroidismmentioning
confidence: 98%